A patient with large retroperitoneal liposarcoma - a challenge for an anesthesiologist - Bojanic, Milica; Radovanović, Dragana; Zahorjanski, Sanja; Škorić-Jokić, Svetlana; Protić, Mlađan (Archive of Oncology, 2022)
Retroperitoneal liposarcoma is a rare type of tumor characterized by slow growth and nonspecific symptoms, and is usually diagnosed at an advanced stage. Patients with huge retroperitoneal liposarcoma have a high risk of developing perioperative complications, and require special preoperative preparation and a carefully planned anesthetic approach. We present the case of a 57-year-old man, who was diagnosed with a huge retroperitoneal liposarcoma, 70 cm in diameter, weighing 30.4 kg and planned for surgical resection of the tumor under general anesthesia. Perioperative treatment and anesthesia for this patient were a great challenge for the anesthesiologist. However, due to preoperative preparation, monitoring and fluid replacement, hemodynamic and respiratory stability of the patient was maintained perioperatively.